Serum Vitamin D Levels, Visual Analog Scale Dysmenorrhea Score, and Endometriosis ASRM Classification: a Relationship Study - Rizany, Selly; Abadi, Adnan; Agustiansyah, Patiyus; Nurtjahyo, Awan; Irfanuddin; Usman, Fatimah; Hartati; Mirani, Putri; Krisna, Ratih; Amran, Rizani; Prasetiyo, Muhammad Ath Thaariq (Indonesian Socety of Obstetrics and Gynecology, 2024)
Objective: To assess the correlation between vitamin D levels, dysmenorrhea intensity measured by the visual analogue scale (VAS), and the stage of endometriosis determined by the American Society of Reproductive Medicine (ASRM) grading score. Methods: A cross-sectional study was conducted involving 37 women diagnosed with suspected endometriosis who met the inclusion and exclusion criteria. The aim was to determine the correlation between vitamin D levels, dysmenorrhea VAS scores, and the ASRM endometriosis stage at RSUP Dr. Mohammad Hoesin Palembang from November 2021 to April 2022. Bivariate analysis was employed to assess correlation, utilizing Pearson's correlation test and the Spearman Rank correlation test as an alternative method. Results: There was a significant positive correlation between vitamin D levels and the VAS score for dysmenorrhea (r = 0.678; p = 0.000) and a very strong positive correlation between vitamin D levels and the degree of endometriosis (r = 0.774; p = 0.000) based on Spearman Rho's correlation test. Conclusion: There is a significant relationship between vitamin D levels with the VAS score of dysmenorrhea and the degree of endometriosis ASRM. Keywords: american society of reproductive medicine, endometriosis, visual analogue scale, vitamin D